2021
DOI: 10.1136/bmjopen-2020-045369
|View full text |Cite
|
Sign up to set email alerts
|

Association between allostatic load and mortality among Chinese older adults: the Chinese Longitudinal Health and Longevity Study

Abstract: BackgroundAllostatic load (AL) has shown that high burden of AL is associated with increased risk of adverse outcomes, but little attention has been paid to China with largest ageing population in the world.ObjectiveThis study is to examine the association between AL and all-cause mortality among Chinese adults aged at least 60 years.DesignPopulation-based prospective cohort study.SettingIn 2011–2012, an ancillary study, in which a blood test was added, including a total of 2439 participants, was conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…For age, we dichotomised at age 60. Some previous studies focused on AL in people aged 60 and above 25 26 and we intuitively found it reasonable to distinguish in the same way between ‘young’ and ‘old’ people in our data; age 60 was furthermore the median age of our study population; and with this age-dichotomisation we avoided violations of the model assumption in the statistical analysis. We dichotomised biomarkers with high-risk values defined as those in the highest quartile of the sex-specific and age-specific distribution, except for HDL-c and albumin, where the lowest quartile was the high-risk value.…”
Section: Methodssupporting
confidence: 58%
“…For age, we dichotomised at age 60. Some previous studies focused on AL in people aged 60 and above 25 26 and we intuitively found it reasonable to distinguish in the same way between ‘young’ and ‘old’ people in our data; age 60 was furthermore the median age of our study population; and with this age-dichotomisation we avoided violations of the model assumption in the statistical analysis. We dichotomised biomarkers with high-risk values defined as those in the highest quartile of the sex-specific and age-specific distribution, except for HDL-c and albumin, where the lowest quartile was the high-risk value.…”
Section: Methodssupporting
confidence: 58%
“…Aggregate cycles of allostasis, the mechanism by which the body maintains homeostasis in response to stress, can result in systemic dysfunction, or “wear and tear,” termed allostatic load. Allostatic load has been evaluated extensively as a health hazard, and high allostatic load has been associated with adverse health outcomes as well as an excess of chronic health conditions (Castagne et al, 2018; Johnston-Brooks et al, 1998; Logan & Barksdale, 2008; Parker et al, 2022; Zhang et al, 2021). Given that allostatic load is cumulative in nature, it has been posited as a potential mechanism responsible for associations between adverse childhood experiences and development of disease later in life (McEwen, 2002; Misiak et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, an individual cannot regain preoperative health or homeostasis. Alternatively, the newly acquired process remains in place long enough to contribute to increased morbidity after several years, even if the change eventually resolves [41]. Allostasis assumes the emergence of a new adaptive balance, which may be beneficial or detrimental to the long-term health of the individual (Figure 1) [37,38].…”
Section: New Paradigm Of Anesthesia Carementioning
confidence: 99%